Slumdogs vs Millionaires: India in the Age of Inequality, Farm Crisis, Food Crisis and the Media - Sainath, P. (JOURNAL OF INDIAN EDUCATION, 2011)
The last 15 years have seen the celebration of the Indian economy as an emerging tiger. And certainly, this is a very different country today from what it was earlier. However, the many achievements and advances have come at a high cost. Inequality in India has grown faster in the last 15 years than it has at any time in the past 50 years. The National Commission for Enterprises in the Unorganised Sector (NCEUS) tells us 836 million Indians live on less than Rs 20 a day, even as the number of dollar billionaires has doubled in five years. The country faces its worst agrarian crisis since the eve of the Green Revolution. Official data show us that over 166,000 farmers committed suicide between 1997 and 2006. Farm incomes have crashed and millions have quit agriculture without proper alternative options. Meanwhile, the media who ought to play the role of informing the public about the direction society has taken are more disconnected from the masses than ever before. Which way are we headed? And can we as a society act differenly?